Polemik Sistem Zonasi PPDB dalam Mewujudkan Pemerataan Pendidikan - Muhammad Sufyan Rabbani; Anissa Nurul Chotimah; Jemima Fathima Pasha (Simpati, 2023)
Equalizing education poses a significant challenge in achieving fair access and equitable opportunities for all students. In an effort to address educational disparities between regions, a zoning system has been implemented in the New Student Admission (PPDB) process. However, this policy has not been without controversy within society. This research aims to analyze the impact and polemics arising from the implementation of the zoning system in the PPDB. The focus of the study is to examine how the application of the zoning system has become a source of debate and controversy among the public. The research utilizes a literature review as the primary approach, collecting data from studies, scholarly articles, research reports, and official documents pertaining to the implementation of the zoning system in the PPDB. Data analysis will consider differing perspectives and arguments that arise in the context of implementing the zoning system. The findings of this research will illustrate the various controversies surrounding the application of the zoning system in the PPDB. This study aims to provide insights into the impact and controversies that arise from the implementation of the zoning system in the PPDB.